Role of apoptosis genes in aggression revealed using combined analysis of ANDSystem gene networks, expression and genomic data in grey rats with aggressive behavior - A. O. Bragin; O. V. Saik; I. V. Chadaeva; P. S. Demenkov; A. L. Markel; Yu. L. Orlov; E. I. Rogaev; I. N. Lavrik; V. A. Ivanisenko (Вавиловский журнал генетики и селекции, 2018)
Aggressive behavior in animals plays an important role in protecting the territory, offspring, establishing social hierarchical relations, etc. Increased aggression is observed in a number of diseases ( schizophrenia, bipolar disorder, brain degenerative disorders). Neuronal apoptosis is crucial in the maintenance of developmental processes during neurogenesis. Alterations in neuronal apoptosis are observed in aging and neuropathologies accompanied by changes in psychoemo tional state (epilepsy, Alzheimer’s disease, neurotrauma). The expression of key neuronal apoptosis genes (Casp3, Bax and Bcl-xl) in the brain of highly aggressive rats is significantly altered. The aim of this work was to analyze associative networks that describe genetic interactions between genes/proteins involved in neuronal apoptosis, differentially expressed genes and genes with polymorphisms in grey rats with aggressive behavior. Analysis revealed 819 differentially expressed genes in the hypothalamus, ventral tegmental region and periaqueductus Sylvii grey matter in grey rats with aggressive and tame behavior. The Stx1a, Mbp and Th genes have the highest index of betweenness centrality in the associative network of differentially expressed genes. Genome analysis revealed 137 polymorphic genes. Three of them (Lig4, Parp1 and Pigt) were involved in neuronal apoptosis. It was shown that polymorphic and differentially expressed genes were statistically significantly overrepresented among ge nes interacting with neuronal apoptosis genes (p value < 0.01). Three moleculargenetic chains describing connections between polymorphic and neuronal apoptosis genes mediated by differentially expressed genes were reconstructed. Chains included the polymorphic genes Tsc1, Adamts4 and Lgals3, differentially expressed genes Ezr, Acan, Th and 19 neuronal apoptosis genes. It was shown that neuronal apoptosis is closely related to aggressive behavior in animals.